Inclusão de jovens com deficiência no mundo do trabalho: análise da participação familiar - Manaia, Marilia Di Vito [UNIFESP] (2015)
The work has been seen as a necessary condition for subsistence of man and also as an important element of production. Throughout history, people with disabilities were excluded from labor field, since society understands that due to physical, sensory and / or mental conditions, those people need assistance and were not able to produce. Regarding people with intellectual disabilities, they have a small percentage of participation in the labor market compared to the other disabilities. When the 8213 Act was designed in 1991, called then Quota Law, the state started to ensure the hiring of those people through quotas. From some professional experience, it is realized young people with intellectual disabilities often live in over-protected family environments which interfere in the acquisition of independence and autonomy. It is understood that this immaturity may be a complicating factor in the integration in the labor market. From this point of view, it is understood that the family has an important role and support to people with intellectual disabilities. This study aimed to analyze the participation of families of young people and adults with intellectual disabilities during the process of inclusion in the world of work which is part of the ?Being Efficient Program in Centro Espírita Beneficente (CEB) "July 30", located in the City of Santos. It was used a methodology based on the case study and the sample chosen were the families who participate in the Program for more than a year, from 2010 to 2013. The survey was conducted through the records of young people / adults in order to identify them. After this survey, we selected four families of young people who are in the inclusion criteria. A qualitative study was conducted through the narratives of families for the inclusion process in the labor market. It was used the speech analysis to evaluate the material collected. The results showed that two out of four families interviewed delegate to the institution the care of their children, being absent of this process and the other two are aware of the child's needs, follow up and assist in this process, taking the responsibility to themselves. In this sense, it was observed that young people and adults with intellectual disabilities, when followed up by the family, mature faster, though within their limits. In order to increase family participation in this process, it was proposed the creation of spaces for discussion and reflection in groups targeting issues related to overprotection, infantilization and achievement of the autonomy in the world of work.